An improved genome assembly for Larimichthys crocea reveals hepcidin gene expansion with diversified regulation and function. (December 2018) - Mu, Yinnan; Huo, Jieying; Guan, Yanyun; Fan, Dingding; Xiao, Xiaoqiang; Wei, Jingguang; Li, Qiuhua; Mu, Pengfei; Ao, Jingqun; Chen, Xinhua
Abstract Larimichthys crocea (large yellow croaker) is a type of perciform fish well known for its peculiar physiological properties and economic value. Here, we constructed an improved version of theL. crocea genome assembly, which contained 26, 100 protein-coding genes. Twenty-four pseudo-chromosomes ofL. crocea were also reconstructed, comprising 90% of the genome assembly. This improved assembly revealed several expansions in gene families associated with olfactory detection, detoxification, and innate immunity. Specifically, six hepcidin genes (LcHamps) were identified inL. crocea, possibly resulting from lineage-specific gene duplication. All LcHamps possessed similar genomic structures and functional domains, but varied substantially with respect to expression pattern, transcriptional regulation, and biological function. LcHamp1 was associated specifically with iron metabolism, while LcHamp2s were functionally diverse, involving in antibacterial activity, antiviral activity, and regulation of intracellular iron metabolism. This functional diversity among gene copies may have allowedL. crocea to adapt to diverse environmental conditions. Yinnan Mu and colleagues present an improved yellow croaker genome, constructed using a hybrid assembly method incorporating long-reads and short-reads. With their improved assembly, the authors found several gene family expansions associated with olfactory detection, detoxification, and innate immunity.